THE DESIGN OF HIGH-RISE HOTEL BUILDING IN LOS-ANGELES,CALIFORNIA,USA - Bazarbayev, Bexultan; Zhumagulova, Aikelbet; Syndarova, Aruzhan; Nurgali, Yelnur; Aldan, Assanali; Mukhtarzhanov, Nurmukhammed (Nazarbayev University School of Engineering and Digital Sciences, 2025)
High-rise building construction presents unique challenges and opportunities in urban areas, particularly in creating vibrant spaces. This capstone project focuses on the design of a 15-storey hotel with two levels of underground parking, strategically ENG 400 13 located in the bustling downtown area of Los Angeles at 1030 S Hill Street. Situated in a seismic zone, the project must adhere to high standards of safety, sustainability, and functionality. The project aims to develop a structure that addresses the city's demand for premium hospitality services while offering innovative solutions for optimizing urban space utilization, implementing sustainable practices, and ensuring compliance with local and international building codes. The goal is to enhance the urban landscape by providing an extraordinary yet environmentally sensitive lodging experience, leveraging modern architectural and engineering principles. This report covers architectural planning, structural and geotechnical design, environmental considerations, and construction management. It explores the complex interplay of technical, environmental, and financial factors, offering detailed design guidance for a high-performance, sustainable building that aligns with the Los Angeles environment.
Design of 15-storey Hotel Building in Los-Angeles, California, USA
Keywords: type of access: open access